Investigation of the physical properties of PLZT ferroelectric ceramics - Effect of the lanthanum content - Guerra, J. D.S.; Silva, A. C. [UNESP]; Mcintosh, R.; Hoque, Mohammad M.; Guo, R.; Bhalla, A. S. (Taylor & Francis, 2015)
In this work, the structural, ferroelectric and dielectric properties, including radio-frequencies and microwave region, has been investigated in Pb1-xLax(ZryTi1-y)1 - (x/4)O3 (PLZT) ferroelectric ceramics, where x = 0.02, 0.04, 0.06, 0.08, 0.10, 0.12 and y = 0.70. Ceramic samples were obtained from the solid-state reaction sintering method, and the dielectric measurements were performed in a wide frequency and temperature region, below and above the paraelectric-ferroelectric (PE-FE) phase transition temperature. The structural properties, investigated at room temperature, from the x-ray diffraction (XRD) technique, revealed the evolution from the rhombohedral (R3m symmetry) to orthorhombic (Pmmm symmetry) phases, with the increase of the lanthanum concentration. The ferroelectric as well as the low frequency dielectric properties revealed a change in the PE-FE phase transition characteristics from a normal to a relaxor behavior, with the increase of the lanthanum content. On the other hand, the high-frequency (microwave) dielectric properties studied at room temperature, showed a strong dielectric dispersion on both normal (x≤0.06) and relaxor (x>0.06) compositions, which indeed revealed to be also strongly dependent on the lanthanum concentration.
Keywords: dielectric properties; ferroelectric ceramics; phase transition; PLZT